The Role of 5-Lipoxygenase and Leukotrienes in Shock and Ischemia-Reperfusion Injury. (2007) - Rossi, Antonietta; Pergola, Carlo; Cuzzocrea, Salvatore; Sautebin, Lidia
Abstract : The leukotrienes (LTs) are metabolic products of arachidonic acid via the 5-lipoxygenase (5-LO) pathway. The biological activities of LTs suggest that they are mediators of acute inflammatory and immediate hypersensitivity responses. In particular, the 5-LO activation has been proposed to be an important regulator for pathogenesis in multicellular organisms. The role of LTs in tissue damage, associated with septic and nonseptic shock and ischemia-reperfusion, has been extensively studied by the use of 5-LO inhibitors, receptor antagonists, and mice with a targeted disruption of the 5-LO gene (5-LOKO). In particular, several data indicate that LTs regulate neutrophil trafficking in damaged tissue in shock and ischemia-reperfusion, mainly through the modulation of adhesion molecule expression. This concept may provide new insights into the interpretation of the protective effect of 5-LO inhibition, which may be useful in the therapy of pathological conditions associated with septic and nonseptic shock and ischemia-reperfusion injury.